Implementation and maintenance of infant dietary diversity in Zimbabwe: Contribution of food and water insecurity - Koyratty, Nadia; Mbuya, Mduduzi N. N.; Jones, Andrew D.; Schuster, Roseanne C.; Kordas, Katarzyna; Majo, Florence D. (Springer, 2022)
Background: Inadequate food and water resources negatively affect child health and the efficiency of nutrition interventions. Methods: We used data from the SHINE trial to investigate the associations of food insecurity (FI) and water insecurity (WI) on mothers’ implementation and maintenance of minimum infant dietary diversity (MIDD). We conducted factor analysis to identify and score dimensions of FI (poor access, household shocks, low availability & quality), and WI (poor access, poor quality and low reliability). MIDD implementation (n = 636) was adequate if infants aged 12 months (M12) ate ≥ four food groups. MIDD maintenance (n = 624) was categorized into four mutually exclusive groups: A (unmet MIDD at both M12 and M18), B (unmet MIDD at M12 only), C (unmet MIDD at M18 only), and D (met MIDD at both M12 and M18). We used multivariable-adjusted binary logistic and multinomial regressions to determine likelihood of MIDD implementation, and of belonging to MIDD maintenance groups A-C (poor maintenance groups), compared to group D, respectively. Results: Low food availability & quality were negatively associated with implementation (OR = 0.81; 0.69, 0.97), and maintenance (ORB = 1.29; 1.07, 1.56). Poor water quality was positively associated with implementation (OR = 1.25; 1.08, 1.44), but inconsistently associated with maintenance, with higher odds of infants being in group C (OR = 1.39; 1.08, 1.79), and lower odds of being in group B (OR = 0.80; 0.66, 0.96). Conclusion: Food security should be prioritized for adequate implementation and maintenance of infant diets during complementary feeding. The inconsistent findings with water quality indicate the need for further research on WI and infant feeding.